Dual-Band Reconfigurable Antenna for Polarization Diversity - Youngje Sung (International Journal of Antennas and Propagation)
This paper proposes a dual-band reconfigurable square-ring antenna with a polarization diversity property. The proposed antenna consists of a square-ring resonator, two stubs with a shorting via, and two PIN diodes. The stub is positioned symmetrically to the left and right of the square-ring resonator, and the square-ring antenna connected to one of two stubs has a dual-band resonance. In this case, both resonant frequencies exhibit linear polarization (LP), and the two polarized waves are perpendicular to each other. The PIN diode selectively connects only one of the two stubs to the square-ring resonator. Thus, the polarization of the proposed antenna changes electrically at the two resonant frequencies. In addition, the frequency ratio (f2/f1) can be easily controlled by changing the length or width of the stub.